Effect of Extraction Solvents on Total Polyphenolic Content and Antioxidant Capacity of Syzygium Aromaticum L. Flower Bud from Ethiopia. (23rd November 2022) - Temesgen, Shibiru; Sasikumar, J. M.; Egigu, Meseret C.
Abstract : In this study, the antioxidative activity and polyphenolic content of Syzygium aromaticum 's flower bud were compared under different extraction solvents including chloroform, ethyl acetate, methanol, and aqueous. The antioxidant activity was assessed via established in vitro assay models such as 2, 2-diphenyl-1-Picrylhydrazyl (DPPH) radical scavenging assay, NO - radical scavenging assay, H2 O2 scavenging assay and Fe 3+ reducing capacity. Total phenolic content was measured according to Folin–Ciocalteu's method, and total flavonoid content was estimated by using the aluminum chloride colorimetric method. The results showed that aqueous extract possessed the highest TPC (19.11 ± 2.76  mg GAE/g DW) and TFC (15.32 ± 1.53  mg CtE/g DW). Among the extracts, methanol extract exerted the strongest radical DPPH quenching activity with an IC50 value of 303.56 ± 13.14   μ g/mL. The highest NO - radical scavenging activity was shown by methanol extract (IC50 192.94 ± 1.9   μ g/mL) which is stronger than BHT (IC50 247.64 ± 12.89   μ g/mL). Methanol extract showed a strong H2 O2 scavenging activity (IC50 233.71 ± 3.72   μ g/mL). The highest Fe 3+ reducing capacity was shown by methanol extract (Absorbance = 0.36 ± 0.05 ). Strong and positive correlations were observed between total phenolic and flavonoid contents and the antioxidant assays. The results of the present work revealed that the tested spice demonstrated high antioxidant activity, total phenolics, and flavonoids. Thus, this spice is worth considering as important source of natural antioxidant agents.